A political economy of Drummond’s poetry - Barbosa, Alexandre de Freitas (Revista do Instituto de Estudos Brasileiros, 2019)
The paper seeks toshed light on José Miguel Wisnik’s contribution in his recent book. He integrates the history of development and mining in Brazil, which had as one of its hallmarks the creation of Rio Doce Valley Corporation (CVRD in Portuguese), and Drummond’s poetic invention, deeply affected by the fate of Itabira, his hometown. Time and space are totally shattered by the process of economic development, but also creatively resignified by the poet who sees the territory of his early sociability buried by the enterprise activity. Vale S.A., as it was renamed in 2007, only after the tragedies of Mariana and Brumadinho seems to convey the poet’s echo of pain, not intelligible by his contemporaries.